trig - d dx(sin-1 x = 1 √ 1 − x 2 d dx(cos-1 x = − 1...

Info iconThis preview shows page 1. Sign up to view the full content.

View Full Document Right Arrow Icon
Review of Trigonometric Functions : courtesy: Chia-Rong Chen sin 2 x + cos 2 x = 1 1 + tan 2 x = sec 2 x 1 + cot 2 x = csc 2 x cos( α ± β ) = cos α cos β sin α sin β sin( α ± β ) = sin α cos β ± cos α sin β sin 2 x = 1 2 (1 cos 2 x ) cos 2 x = 1 2 (1 + cos 2 x ) d dx (sin x ) = cos x d dx (cos x ) = sin x d dx (tan x ) = sec 2 x d dx (cot x ) = csc 2 x d dx (sec x ) = sec x tan x d dx (csc x ) = csc x cot x Derivatives of Inverse Trigonometric Functions
Background image of page 1
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: : d dx (sin-1 x ) = 1 √ 1 − x 2 d dx (cos-1 x ) = − 1 √ 1 − x 2 d dx (tan-1 x ) = 1 1 + x 2 d dx (cot-1 x ) = − 1 1 + x 2 d dx (sec-1 x ) = 1 x √ x 2 − 1 d dx (csc-1 x ) = − 1 x √ x 2 − 1 1...
View Full Document

This note was uploaded on 02/11/2009 for the course ENTC 219 taught by Professor Staff during the Spring '08 term at Texas A&M.

Ask a homework question - tutors are online